2006
DOI: 10.1016/j.buildenv.2005.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Transient CFD simulation of the respiration process and inter-person exposure assessment

Abstract: It is known that the person-to-person spreading of certain infectious diseases is related with the transmission of human exhaled air in the indoor environments, and this is suspected to be the case with the severe acute respiratory syndrome (SARS) outbreak. This paper presents the numerical analysis of the human respiration process and the transport of exhaled air by breathing, sneezing, and coughing and their potential impact on the adjacent person in a modeled room with displacement ventilation. In order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
124
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(128 citation statements)
references
References 8 publications
2
124
2
Order By: Relevance
“…However, most of these studies were limited to numerical analyses. Gao and Niu (2006) carried out a numerical study in a room with two persons sitting opposite to each other. They found that cross infection may occur because of the long distances traveled by the sneezed air in a specific direction.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these studies were limited to numerical analyses. Gao and Niu (2006) carried out a numerical study in a room with two persons sitting opposite to each other. They found that cross infection may occur because of the long distances traveled by the sneezed air in a specific direction.…”
Section: Introductionmentioning
confidence: 99%
“…[6e18]) by replacing it by the high-Reynolds number eddy viscosity formulation of the standard keε turbulence model (see Table 1). However, as known and highlighted by several authors, the airflow in some regions of a climatized room is not fully turbulent [19,20] and, therefore, using this high-Reynolds number equation for the effective viscosity may overestimate the turbulent diffusion.…”
Section: Effective Viscosity Modellingmentioning
confidence: 96%
“…These results are supported by those of Craven and Settles [18] who modelled the thermal plume from a highly simplified human model with the RNG keε model concluding that the predictions agree quite well with the 2D PIV measured data. Gao and Niu [19] used the RNG keε model, with a differential equation to obtain the effective viscosity at low-Reynolds number when simulating the airflow around a seated human body in a displacement ventilated room, confirming that such model has the potential to adequately predict the spread mechanisms of exhaled pollutants. However, the authors did not assess or validate with experiments the model predictions.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other researchers have numerically studied the transport of bacteria through an expiratory process in an isolation room (Zhao et al 2009;Richmond-Bryant 2009;Huang and Tsao 2005). The detailed features of body geometry have also been examined in a study of personal exposure when two occupants are positioned opposite each other (Gao and Niu 2006). In comparison with the outcomes of numerical modeling, the experimental results obtained in this latter study were limited and far from complete.…”
Section: Introductionmentioning
confidence: 99%